2021
DOI: 10.1177/23259671211021825
|View full text |Cite
|
Sign up to set email alerts
|

Return-to-Sport Criteria After Upper Extremity Surgery in Athletes—A Scoping Review, Part 2: Ulnar Collateral Ligament of the Elbow Procedures

Abstract: Background: There is a lack of consensus to guide patient return to sport (RTS) after elbow ulnar collateral ligament surgery (eUCLS). Purpose: To describe the reported RTS criteria after eUCLS in the athletic population. Study Design: Scoping review; Level of evidence, 4. Methods: This scoping review was performed by adhering to the PRISMA-ScR (Preferred Reporting Items for Systematic Reviews and Meta-Analyses–Scoping Review) guidelines. We searched 5 electronic databases (MEDLINE, Scopus, SPORTDiscus, Embase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…However, there was no consensus on how much time was adequate for rehabilitation before returning, with time frames ranging from 4-16 months. 38 Conversely, in a separate systematic review the most common return to play criterion was completion of an ITP (87%; 13 out of 15 studies) and found players started the ITP on average 16.7 weeks after surgery (range 12-18 weeks). 39 The optimal wait period following injury or surgery to initiate an ITP is likely highly individualized.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, there was no consensus on how much time was adequate for rehabilitation before returning, with time frames ranging from 4-16 months. 38 Conversely, in a separate systematic review the most common return to play criterion was completion of an ITP (87%; 13 out of 15 studies) and found players started the ITP on average 16.7 weeks after surgery (range 12-18 weeks). 39 The optimal wait period following injury or surgery to initiate an ITP is likely highly individualized.…”
Section: Discussionmentioning
confidence: 97%
“…37 Many factors can influence the ideal time course for initiating an ITP, such as time from surgery, level of competition, time of season, surgeon's preference, and successful progression through physical therapy. In a recent review, Griffith et al 38 included 14 studies tracking return to sport (RTS) after UCLr and reported time from surgery was the most common RTS criterion used and was reported in 100% of the studies. However, there was no consensus on how much time was adequate for rehabilitation before returning, with time frames ranging from 4-16 months.…”
Section: Discussionmentioning
confidence: 99%